2006
DOI: 10.1016/j.scitotenv.2006.09.001
|View full text |Cite
|
Sign up to set email alerts
|

The effect of home characteristics on dust antigen concentrations and loads in homes

Abstract: On-site home visits, consisting of a home inspection, dust sampling, and questionnaires were conducted in 777 homes belonging to an ongoing birth cohort study in Cincinnati, Ohio. Various home characteristics were investigated, and antigen levels (concentrations [μg/g] and loadings [μg/ m 2 ]; IU for cockroach allergen) in floor dust samples collected in child's primary activity room were analyzed by ELISA. Monoclonal antibodies were used for the analysis of cat, house dust mite, and cockroach allergens, and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
59
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(60 citation statements)
references
References 46 publications
0
59
1
Order By: Relevance
“…Salo et al (2005) and Cho et al (2006) found a significant relationship between Alternaria antigen concentration and the presence of dogs in the house, while the present study and that of Emberlin et al (1995) did not confirm any correlation between concentration of culturable fungi and the presence of pets.…”
Section: Relationship Between Concentration Of Culturable Fungi and Fcontrasting
confidence: 89%
See 2 more Smart Citations
“…Salo et al (2005) and Cho et al (2006) found a significant relationship between Alternaria antigen concentration and the presence of dogs in the house, while the present study and that of Emberlin et al (1995) did not confirm any correlation between concentration of culturable fungi and the presence of pets.…”
Section: Relationship Between Concentration Of Culturable Fungi and Fcontrasting
confidence: 89%
“…In homes of those children the most common fungi were Cladosporium, Penicillium, Aspergillus and Alternaria. Furthermore, Cho et al (2006) stated that the level of Alternaria antigen was associated with some home characteristics and activity of the inhabitants.…”
Section: Composition and Concentration Of Culturable Fungi In Differementioning
confidence: 99%
See 1 more Smart Citation
“…Although this method is convenient and favourable, questionnaire-based methods are difficult to validate against microbial measurements [40,48]. Numerous studies validated self-reported visible mould questions against inspector-reported observations [36,31,[78][79][80][81] and did not find any evidence for over-or underreporting of dampness and mould by occupants.…”
Section: Validity Of Exposure Assessmentmentioning
confidence: 99%
“…This does not agree with some prior reports (Jaakkola, Parise et al 2004). On the other hand, the findings suggest that any benefit may diminish over time, perhaps as the carpet inevitably accumulates particles, including fungi and allergens, with normal use and maintenance (Dybendal, Vik et al 1989;Dybendal, Vik et al 1990;Dybendal and Elsayed 1992;Cho, Reponen et al 2006;Giovannangelo, Gehring et al 2007). Unfortunately, the data did not include specific age of carpets older than one year.…”
Section: Discussionmentioning
confidence: 99%